2017
DOI: 10.3847/1538-4357/aa88c3
|View full text |Cite|
|
Sign up to set email alerts
|

Wavelet Denoising of Radio Observations of Rotating Radio Transients (RRATs): Improved Timing Parameters for Eight RRATs

Abstract: Rotating radio transients (RRATs) are sporadically emitting pulsars detectable only through searches for single pulses. While over 100 RRATs have been detected, only a small fraction (roughly 20%) have phase-connected timing solutions, which are critical for determining how they relate to other neutron star populations. Detecting more pulses in order to achieve solutions is a key to understanding their physical nature. Astronomical signals collected by radio telescopes contain noise from many sources, making t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Wavelet analysis is a powerful time-frequency analysis method, like Fourier transform, which is particularly suitable for processing unstable signals such as complex noise or sudden changes in the data. Although this method is effective and has been applied in some fields of astronomy such as white dwarf [83] and pulsar [84,85], it has not yet been widely used in pulsar data processing from our knowledge. Perhaps the method of wavelet analysis will be helpful for the measurement of a braking index in the future [84].…”
Section: Measurement Of Braking Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Wavelet analysis is a powerful time-frequency analysis method, like Fourier transform, which is particularly suitable for processing unstable signals such as complex noise or sudden changes in the data. Although this method is effective and has been applied in some fields of astronomy such as white dwarf [83] and pulsar [84,85], it has not yet been widely used in pulsar data processing from our knowledge. Perhaps the method of wavelet analysis will be helpful for the measurement of a braking index in the future [84].…”
Section: Measurement Of Braking Indexmentioning
confidence: 99%
“…Although this method is effective and has been applied in some fields of astronomy such as white dwarf [83] and pulsar [84,85], it has not yet been widely used in pulsar data processing from our knowledge. Perhaps the method of wavelet analysis will be helpful for the measurement of a braking index in the future [84]. Furthermore, due to the James Webb Space Telescope having been successfully launched and operated [86], more details of the Crab nebula will be discovered and analyzed.…”
Section: Measurement Of Braking Indexmentioning
confidence: 99%
“…It is effective for suppressing the terrestrial interference. Jiang et al [15] presented a wavelet based denoised approach for the de-dispersed time series which is utilized before the single-pulse search. Based on the a priori knowledge of the spin period of RRATs, they applied wavelet reconstruction and shrinkage to the selective frequency bands.…”
Section: Related Workmentioning
confidence: 99%
“…Weak pulse analyses have been performed for RRATs (e.g. Cui et al 2017;Jiang et al 2017) and recent work by Bhattacharyya et al (2018) has found that PSR J1913+1330 exhibits a weak mode emission followed by long periods where there is no detectable emission. A lack of bright pulses could explain why our pulse wait-time distribution appears to support purely random emission, and does not show the secondary component seen in PSR J1819−1458 and PSR J1317−5759.…”
Section: Wait-time Distribution Analysismentioning
confidence: 99%